Analisis Saluran Pemasaran Jeruk Manis (Citrus sinensis L.) di Desa Barung Kersap Kecamatan munte Kabupaten Karo - Purba, Dionisius; Salqaura, Siti Sabrina (Universitas Medan Area, 2025)
This article or writing aims to analyze marketing channels, marketing margins and marketing efficiency of sweet oranges in Barung Kersap Village, Munte District, Karo Regency. The problem is focused on the analysis of Sweet Orange Marketing channels. In order to approach this problem, theoretical references from Kotler, Fandeli, and Mulyadi are used. The data used are primary and secondary data and are analyzed qualitatively and quantitatively. This study concludes that the marketing channel is at level three and in Barung Kersap Village there is only one marketing channel. The largest marketing margin is at wholesalers of Rp 6,500 with a percentage of 33%. For marketing efficiency, all institutions are considered efficient and the most efficient are collectors and wholesalers.